Aldosterone in the brain and cognition: knowns and unknowns - Nieckarz, Anna; Graff, Beata; Burnier, Michel; Marcinkowska, Anna B.; Narkiewicz, Krzysztof (Frontiers in Endocrinology, 2024)
Mineralocorticoid receptors are expressed in several structures of the central nervous system, and aldosterone levels can be measured in the brain, although in smaller amounts than in the plasma. Nevertheless, these amounts appear to be sufficient to elicit substantial clinical effects. Primary aldosteronism, characterized by high levels of plasma aldosterone, is one of the most common causes of secondary hypertension. In this context, high aldosterone levels may have both indirect and direct effects on the brain with a negative impact on several cerebral functions. Thus, chronic aldosterone excess has been associated with symptoms of anxiety and depressiontwo clinical entities themselves associated with cognitive deficits.Today, there is an increasing number of reports on the influence of aldosterone on the brain, but there is also a significant amount of uncertainty, such as the role of high aldosterone levels on cognitive functions and decline independently of blood pressure. In this mini review, we discuss the known and unknowns of the impact of aldosterone on the brain putting emphasis on cognitive functions.